PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANDROID UNTUK MENINGKATKAN HASIL BELAJAR EKONOMI DI SMA - Dani Kurniawati; Mohamad Arief Rafsanjani (FKIP Unswagati, 2023)
This is motivated by the low learning outcomes of students on the material price index and inflation. This is due to a lack of understanding of the material and the limitations of the learning media used for the learning delivery process. So this development research aims to find out how Android-based interactive media can improve student learning outcomes. This R&D research uses the thiagarajan model known as 4D namely Define, Design, Develop, and Disseminate. The subjects of this research were students of class XI IPS 2 at SMAN 15 Surabaya, which consisted of 34 students. Android-based interactive media obtained a material validity feasibility value of 97% and media experts 95%, namely with a very feasible interpretation. Meanwhile, the students' responses obtained a score of 96% with a very proper interpretation. In measuring the increase in learning outcomes carried out by the N-Gain test which obtained a result of 0.69 which is included in the medium category. Therefore it can be seen that there is an increase in student learning outcomes. This increase occurred because the presentation of media designs that were developed was attractive and fun, supplemented by animated video illustrations of material, supplemented by learning evaluations with multilevel methods, ease of operation and flexible use of media, and media designed interactively to increase student motivation in obtaining better learning outcomes. better. So the conclusion that is obtained is that Android-based interactive media is recommended for use in the learning process and is able to improve student learning outcomes.